Bioprospecção de leveduras fermentadoras de xilose visando a produção de etanol a partir de bagaço de cana-de-açúcar - Silva, Rosimeire Oenning da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The biomass lignocellulosic is an source alternative for the production of etha-nol. Among the substrates produced in Brazil sugar cane bagasse is abundant and available. Compatible with the generation of bagasse use would be the production ethanol. Two ways are possible hydrolysis of bagasse, the chemical and enzymatic. Whatever the route of the hydrolysis the must contain D-xylose to be the most abun-dant pentose in the constitution of the lignocellulosic material. The availability of mi-cro-organisms that ferment pentose sugars is essential for the development of pro-cesses for production of hemicellulosic ethanol. To overcome this limitation the re-search sought to select strains of yeast capable of converting xylose present in the semisynthetic medium and hemicellulose in bagasse hydrolyzate of cane sugar into ethanol. To both samples was performed on samples of flowers and cane juice and isolation of the strains was done in medium containing xylose as a carbon source. There was screened by means of biological tests for the evaluation of ethanol pro-duction following the methodology for screening plates. The yeasts that showed posi-tive responses in the test plates were identified through sequencing of D1 / D2 do-mains of the rDNA. A total of one hundred sixty-five isolates, four were selected for their possible ability to ferment D-xylose. These Yeast were idenfified as Wicker-hamomyces anomalus, Schizosaccharomyces pombe and Starmerella meliponino-rum. Quantitative evaluation of ethanol production from xylose were made and for comparison were also evaluated ethanol production from glucose. The yeast that produced ethanol in semisynthetic medium were selected for fermentation of hemi-cellulose hydrolyzate bagasse cane sugar. For this evaluation sugarcane bagasse was subjected to acidic hydrolysis and concentrated detoxified with active charcoal. Cell growth and viability by counting in a Neubauer chamber, glucose, xylose, xylitol ...

A biomassa lignocelulósica é fonte alternativa para a produção de etanol. Entre os substratos produzidos no Brasil, o bagaço de cana-de-açúcar é abundante e disponível. Um uso compatível com a geração do bagaço seria a produção de etanol. Duas formas de hidrólise do bagaço são possíveis, a química e a enzimática. Qualquer que seja a via de hidrólise, o mosto conterá D-xilose por ser a pentose mais abundante na constituição do material lignocelulósico. A disponibilidade de mi-cro-organismos que fermentam pentoses é imprescindível para desenvolvimento de processos de produção de etanol hemicelulósico. Para contornar essa limitação, a pesquisa buscou selecionar cepas de leveduras capazes de converter em etanol a xilose presente no meio semissintético e no hidrolisado hemicelulósico de bagaço de cana-de-açúcar. Para tanto realizou-se coletas de amostras de caldo de cana e flo-res, e o isolamento das cepas foi feito em meio contendo xilose como fonte de carbono. Fez-se uma triagem por meio dos testes biológicos de avaliação de produção de etanol seguindo a metodologia de rastreio em placas. As leveduras que apresentaram respostas positivas no teste das placas foram identificadas por meio do sequenciamento dos domínios D1/D2 do rDNA. De um total de cento e sessenta e cinco cepas isoladas, quatro foram selecionadas por sua possível capacidade de fer-mentar D-xilose. Essas leveduras foram identificadas como Wickerhamomyces ano-malus, Schizosaccharomyces pombe e Starmerella meliponinorum. Foram feitas avaliações quantitativas da produção de etanol a partir da xilose e, para fins de comparação, também foi avaliada a produção de etanol a partir da glicose. As leve-duras que produziram etanol em meio semissintético foram selecionadas para fer-mentação em hidrolisado hemicelulósico de bagaço de cana-de-açúcar. Para essa avaliação, o bagaço de cana foi submetido à hidrólise ácida...
Bioprospecting of xylose-fermenting yeasts aiming to produce ethanol from bagasse cane sugar
Keywords: Microbiologia industrial; Levedos - Aplicações industriais; Fermentação; Bagaço de cana - Microbiologia; Hemicelulose; Etanol